Relationship between Green Financing and Investment Logic and Effectiveness Evaluation of Financing Decisions - Lei Kong; Yu Lei; Qian Zhang; Jing Zhang; Xingzhi Guo; Daoyuan Shi (Discrete Dynamics in Nature and Society)
Green financing diverts more funds to green industries such as environmental protection, and clean energy, enabling the industries to realize structural adjustment. On green financing, the existing studies at home and abroad mainly focus on the definition of concepts and service scope and system construction. There are few attempts to combined green financing efficacy with corporate investment from the angles of investment level, investment efficiency, and investment risks. This paper associates green financing policy with corporate investment, analyzes the logical connection between the two, and thereby evaluates the effectiveness of green financing decisions. Specifically, a decision model was established for the government participation in green financing via green product subsidy, and a solving algorithm was developed for the model. After that, the authors analyzed the correlations of green financing with the investment level and investment efficiency of green enterprises. Next, the effectiveness of green financing decisions was discussed under dynamic operation risks. Finally, the proposed approach was demonstrated through simulation and empirical analysis.